Moso bamboo and Japanese cedar seedlings differently affected soil N2O emissions. (22nd August 2021) - Fang, Haifu; Gao, Yu; Zhang, Qiang; Ma, Lili; Wang, Baihui; Shad, Nasir; Deng, Wenping; Liu, Xiaojun; Liu, Yuanqiu; Zhang, Ling
Abstract: Moso bamboo expansions into Japanese cedar forests are common. The expansion effects on soil nitrous oxide (N2 O) emissions have not been thoroughly understood, and the underlying microbial mechanisms remain unclear. We studied bacterial and fungal contribution to soil N2 O emissions under moso bamboo or Japanese cedar by applying bacterial or fungal inhibitors using streptomycin and iprodione, respectively. Soil N2 O emissions were measured and the relative contribution of bacteria and fungi to soil N2 O emissions was calculated. N2 O emission from soil with moso bamboo was significantly higher than under Japanese cedar. Compared with control, bacterial or fungal inhibitor or their combination decreased N2 O emissions, indicating substantial contribution of microbial activities to N2 O emissions. However, the relative contribution of bacteria and fungi to N2 O emissions was not affected by plants. Soil organic carbon, total and ammonium nitrogen were lower in soil under moso bamboo than Japanese cedar, suggesting faster microbial decomposition under moso bamboo. Fungal inhibitor and plants interactively affected soil pH, total phosphorus and ammonium nitrogen, while bacterial inhibitor and plants interactively affected total nitrogen, indicating substantial dependence of effects by microbial communities on plant species. Moso bamboo and Japanese cedar differed in their effects on soil N2 O emissions with higher emissions under moso bamboo. Stimulation of N2 O emission under moso bamboo might occur due to higher nitrogen mineralization and subsequent denitrification induced by high root exudation. These results highlight the need to consider the effect of species shifts on N2 O emissions in forests.